2020
DOI: 10.1111/jce.14672
|View full text |Cite
|
Sign up to set email alerts
|

His bundle pacing insights from electroanatomical mapping: Topography and pacing targets

Abstract: has a modest consulting relationship with Abbott, Boston Scientific, and is a recipient of a research grant from Boston Scientific. Daniel McKelvey is an employee of Abbott. David Casavant and AJ. Monin are employees of Boston Scientific. Mikhail Maslov became an employee of Novartis after his work on the paper was completed. Other authors: No disclosures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…68 Moreover, efforts to circumvent the difficulties of locating the conduction system with fluoroscopy are being made by testing new 3D electro-anatomical mapping systems. 69 Recently published data is also encouraging for an electrogram-only guided approach to HBP with minimal fluoroscopy and high success rates compared to the classical method. 70 But of course, the need for data collection through conducting large RCTs, which will prove the significant benefit of this pacing in clinical endpoints of hospitalizations and mortality, should not be overlooked.…”
Section: Looking To the Futurementioning
confidence: 90%
“…68 Moreover, efforts to circumvent the difficulties of locating the conduction system with fluoroscopy are being made by testing new 3D electro-anatomical mapping systems. 69 Recently published data is also encouraging for an electrogram-only guided approach to HBP with minimal fluoroscopy and high success rates compared to the classical method. 70 But of course, the need for data collection through conducting large RCTs, which will prove the significant benefit of this pacing in clinical endpoints of hospitalizations and mortality, should not be overlooked.…”
Section: Looking To the Futurementioning
confidence: 90%
“…Therefore, it has been speculated that in NS-HBP the tissue activated local to the right-sided His bundle and the right-sided His lead electrode would be right ventricular myocardium. 10 Thus, RV activation would be mainly affected by NS-HBP, preserving LV synchrony. Whereas in RVP, BVP, and BBB (other causes of wide QRS), dyssynchronous left ventricular activation is expected and has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Although feasibility trials and retrospective studies have shown promising results, the role of EAM in routine practice for physiologic lead placement requires further investigation 7–10,13,14 . The additional time needed to create electroanatomic maps and associated financial costs should be considered when selecting appropriate patients.…”
Section: Discussionmentioning
confidence: 99%